1997
DOI: 10.1111/j.1748-5827.1997.tb02987.x
|View full text |Cite
|
Sign up to set email alerts
|

New combination for the therapy of canine otitis externa I Microbiology of otitis externa

Abstract: In order to compound a new drug combination against canine otitis externa (OE), 515 dogs affected with OE were subjected to physical examination and microbiological analysis of their ear exudates. OE was erythematous-ceruminous in 83 per cent and suppurative in 17 per cent of the patient material. Erythematous-ceruminous inflammations were characterised by severe pruritus and accumulation of brownish, greasy cerumen in the auditory canal. The yeast Malassezia pachydermatis was isolated from the ears of 76 per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
63
2
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 12 publications
22
63
2
6
Order By: Relevance
“…Kiss et al (1997) reported high (63%) prevalence of Malassezia yeasts in otitis of animals 2-5 years old. Contrarily, according to our study the risk group seems to be the group of geriatric animals, with 63.3% prevalence of Malassezia infection.…”
Section: Discussionmentioning
confidence: 97%
“…Kiss et al (1997) reported high (63%) prevalence of Malassezia yeasts in otitis of animals 2-5 years old. Contrarily, according to our study the risk group seems to be the group of geriatric animals, with 63.3% prevalence of Malassezia infection.…”
Section: Discussionmentioning
confidence: 97%
“…Many research groups have studied culture and sensitivity characteristics 4,13,20,25,33,34 , but the results (and, indeed, results from individual cases) are quite difficult to translate into definite treatment recommendations. Agreement between cytology and culture is not always good.…”
Section: Additional Procedures For Chronic and Recurrent Otitismentioning
confidence: 99%
“…Inappropriate and/or long-term use of antibacterial agents can cause bacterial resistance; some authors therefore recommend that more potent and broad-spectrum antibiotics such as gentamicin and chloramphenicol should not be used as first-choice treatments 18 . 25,36,58 . Ketoconazole is considered the most effective of these.…”
Section: Antibacterialsmentioning
confidence: 99%
“…Otitis externa (OE) is common in dogs and is a disease of multifarious etiology. The yeast and bacterium most frequently isolated from OE dogs are Malassezia pachydermatis and Staphylococcus intermedius [2,11,20,23], respectively. Staphylococci including S. intermedius are present in the nasal vestibulum, external auditory meatus, intestinal and urinogenital tracts, anal mucosa, and on the skin surface of dogs.…”
mentioning
confidence: 99%